The Pro-Import Effect of Immigrants. Reviewing Lessons from The Mass Migration To The Americas - Nastasi, Federico (Revista Uruguaya de Historia Económica, 2021)
Abstract: There is a vast consensus in economics about the positive impact of migration on trade flows. Estimations, mainly based on augmented gravity model, usually present a higher elasticity of import than export flows. Why do immigrants affect more imports than exports in the host-country? This is probably due to the coexistence of two forces that foster import flow: the preference channel and the network channel, whereas export benefits only from the last one. It is technically difficult to disentangle the two effects, but it is known that there is ‘something’ impacting more on imports than on exports. This ‘something’ seems to be the migrants’ bias for home products. This paper provides a critical and comprehensive review of the related literature. Its main innovation is not based on empirical results but rather on an original interpretation of previous work, with an original focus on the pro-import effect of immigrants and on their impact on consumption in the host country, as most of the studies on the effects of immigration focus on production effects.
Keywords: Business history in Latin America